Desempenho dos estudantes de enfermagem na realização do banho no leito em treino de habilidade e em cenário simulado: um ensaio clínico controlado randomizado - Miranda, Renata Pinto Ribeiro (2016)
This study aimed to evaluate the effectiveness of skills training and simulated scenario in cognitive knowledge, practical performance and satisfaction of nursing students during education in bed bath. This is a clinical trial, controlled and randomized trial comparing the skills training and the simulated scenario, formed by 58 students of the 5th period of nursing degree in two educational institutions in the southern state of Minas Gerais. In the first phase of the study, all students participated in the exhibition of a dialogic class about bed bath. Soon the end of the class they were all sent to the laboratory and observed the researcher perform care on a low-fidelity mannequin. At the end of the demonstration a randomization was performed by coin toss, in which 28 students formed the control group (CG) and 30 students formed the Simulated Group (GS). In the second stage of the study GC students performed the bed bath at training skills with low-fidelity mannequin in the nursing lab and GS students performed the careful simulated scenario with an actor patient. At the end of the simulated scenario the students of GS participated in the debriefing, based on three questions: How did you feel attending this patient? What were your positive actions? What would you do differently? To achieve the objectives were developed four instruments, which have undergone a process of refinement and content analysis of five judges. Assessments were made through these instruments, about the cognitive and practical knowledge on the subject and pleased to participate in these teaching strategies in various stages of research. In the third stage of the study was the follow up, at which point there was a loss of six students, staying in that phase of the study on GC = 25 and GS = 27 students. At that moment the students were assessed again on the cognitive knowledge on the subject and how much satisfaction. In October and November 2014 we conducted a pilot test with 15 students of both institutions. Results allowed identified that the acquisition and assimilation of cognitive knowledge was significantly higher in the simulation group. The performance was similar in both groups regardless of the teaching strategy, and in some actions the GC performed better and in others the GS. Regarding satisfaction both groups had high scores, however, the GS showed higher overall satisfaction and remained even after 30 days (follow up). One can observe the end of the study that simulated scenario assisted in the acquisition and retention of knowledge and that both strategies have provided the practical performance students on the studied subject, but the GS showed higher satisfaction and during the debriefing these acknowledged their mistakes and the actions that could have done differently in order to provide an effective recovery for the patient.